ANALISIS FASIES DAN PERMODELAN SIKUEN STRATIGRAFI BATUAN KARBONAT LINTASAN KORIDO, FORMASI WAINUKENDI, KABUPATEN SUPIORI, PAPUA - Joshua Shima; Hadi Nugroho; Fahrudin Fahrudin; Asep Kurnia Permana (Geological Engineering E-Journal, 2014)
Korido is located in Supiori District , Papua , Indonesia . This area is in the north of the Central Range and included in the North Irian Basin which is the fore arc basin (Mc Adoo & J.C. Haebig, 1999). Own research area based on geology map created by Masria et al ( 1981) composed by Wainukendi Formation which is composed predominantly by carbonate sedimentary rocks .The purpose of this study is to determine the pattern of lithology and lithological boundaries were obtained from measured stratigraphy along the trajectory of research which is then integrated with the micro facies analysis and facies zone were obtained by petrographic analysis to determine the depositional environment and depositional processes that occur in Wainukendi Formation. More over, the relative age determination is also done based on the analysis of large benthic foraminifera so the deposition process can be integrated with relative age . The ultimate goal of this research is to integrate field data, micro facies analysis results and deposition process analysis results to create a model of sedimentation, determining stratigraphic marker, and the determines system tract that develops in Wainukendi Formation in the study area .The method used in this research is geological mapping focused on stratigraphy subjects in Korido area to get  lithostratigraphy sequence, platform type, sedimentation processes, and laboratory analysis include petrographic analysis to determine micro facies and facies zone and paleontological analysis to determine the relative age which then integrated to obtain stratigraphic marker and systems tract that develops in Wainukendi Formation. From the analysis of platform type showed the type of platform existing in this area is rimmed shelf type which is then used as a reference in micro facies analysis according to Wilson (1975) to obtain 4 facies zone that exist in this study area is reef platform margin , slope , toe of slope apron and deep shelf . Based on the analysis of the deposition process obtained 3 cycles of sedimentation that occurred from Wainukendi Formation . From the results of this analysis are used in determining the stratigraphic sequence to obtain stacking patterns that evolve based sequence boundary and its systems tract is composed of LST - TS - MFS - TST - HST so that obtain a full cycle changes in accommodation space and sediment supply where there is an increase in accommodation space which was offset by an increase in the supply of sediment in LST phase is characterized by progradation and agradation, an increase in the supply of sediment is lower than the increase in accomodation space in TST phase is characterized by retrogradation, and lastly, a decrease in accommodation space while sediment supply rate is still high in HST phase characterized by progradation.